Impact of disease burden and late loss of B cell aplasia on the risk of relapse after CD19 chimeric antigen receptor T Cell (Tisagenlecleucel) infusion in pediatric and young adult patients with relapse/refractory acute lymphoblastic leukemia: role of B-cell monitoring - Molinos-Quintana, Águeda; Alonso-Saladrigues, Anna; Herrero, Blanca; Caballero-Velázquez, Teresa; Galán-Gómez, Víctor; Panesso, Melissa; Torrebadell, Montserrat; Delgado-Serrano, Javier; Pérez de Soto, Concepción; Faura, Anna; González-Martínez, Berta; Castillo-Robleda, Ana; et al. (Frontiers in Immunology, 2024)
Loss of B-cell aplasia (BCA) is a well-known marker of functional loss of CD19 CAR-T. Most relapses and loss of BCA occur in the first months after CD19 CAR-T infusion. In addition, high tumor burden (HTB) has shown to have a strong impact on relapse, especially in CD19-negative. However, little is known about the impact of late loss of BCA or the relationship between BCA and pre-infusion tumor burden in patients infused with tisagenlecleucel for relapsed/refractory B-cell acute lymphoblastic leukemia. Therefore, the optimal management of patients with loss of BCA is yet to be defined. We conducted a Spanish, multicentre, retrospective study in patients infused with tisagenlecleucel after marketing authorization. A total of 73 consecutively treated patients were evaluated. Prior to infusion, 39 patients had HTB (> 5% bone marrow blasts) whereas 34 had a low tumor burden (LTB) (<5% blasts). Complete remission was achieved in 90.4% of patients, of whom 59% relapsed. HTB was associated with inferior outcomes, with a 12-month EFS of 19.3% compared to 67.2% in patients with LTB (p<0.001) with a median follow-up of 13.5 months (95% CI 12.4 – 16.2). In the HTB subgroup relapses were mainly CD19 negative (72%) whereas in the LTB subgroup they were mainly CD19 positive (71%) (p=0.017). In the LTB group, all CD19-positive relapses were preceded by loss of BCA whereas only 57% (4/7) of HTB patients experienced CD19-positive relapse. We found a positive correlation between loss of BCA and CD19 positive relapse (R-squared: 74) which persisted beyond six months post-infusion. We also explored B-cell recovery over time using two different definitions of loss of BCA and found a few discrepancies. Interestingly, transient immature B-cell recovery followed by BCA was observed in two pediatric patients. In conclusion, HTB has an unfavorable impact on EFS and allo-SCT might be considered in all patients with HTB, regardless of BCA. In LTB patients, loss of BCA preceded all CD19-positive relapses which were also frequent in patients who lost BCA beyond six months post-infusion. Therefore, these patients are still at significant risk for relapse and close MRD monitoring and/or therapeutic interventions should be considered